Retinal nerve fibre layer thickness measurements using optical coherence tomography in migraine patients. Issue 8 (9th July 2008) - Martinez, A; Proupim, N; Sanchez, M
Abstract : Aim: To compare the retinal nerve fibre layer (RNFL) thickness in eyes of migraine patients with age-matched healthy subjects using optical coherence tomography. Methods: The study was designed as an observational cross-sectional study. 70 eyes of 70 patients (mean age 28.2 (SD 7.9) years) with migraine with or without aura according to the criteria of the Headache International Society and 53 eyes of 53 age-matched healthy controls (mean age 28.0 (8.1) years) were included. Optical coherence tomography was performed with the Stratus OCT (model 3000, software ver. 4.0.2; Carl Zeiss Meditec, Dublin, CA) after pupillary dilation. The fast RNFL thickness (3.4) scan acquisition protocol was used. Results: In the migraine group, the mean Migraine Disability Assessment Score (MIDAS), the mean number of attacks per 3 months, and the length of migraine history were 34.3 (15.2), 17.0 (6.7) and 14.8 (5.6), respectively. The RNFL average thickness in the migraine was within the normal range, but the temporal quadrant RNFL thickness in the migraine patients was significantly lower than that of the control group, 62.2 (10.8) μm vs 70.8 (12.4) μm, respectively (p = 0.0001). However, there was no difference between migraineurs and controls in the superior, inferior, and nasal quadrants, p = 0.8810, p = 0.1531, and p = 0.8300, respectively. Within the migraine group, the average RNFL thickness was significantly correlated with the MIDAS disability score (r = −0.93, p<0.0001) and the frequency of migraine attacks (r = −0.86, p<0.0001). There were no statistically significant differences, between study groups, in disc area or cup/disc area ratio, p = 0.8102 and p = 0.7236, respectively. Considering the clinical examination, RNFL, and optic disc parameters, no one in the migraine group was qualified as having glaucomatous damage. Conclusion: The RNFL in the temporal quadrant was found to be thinner in migraine patients. In addition, we found a strong correlation between migraine severity and the RNFL average thickness parameters.